Investigation of ultrasound mediated extravasation of a model drug by perfluorobutane nanodroplets - Wu, Q; Choi, V; Bau, L; Carugo, D; Evans, ND; Stride, E (Elsevier, 2024)
Objective: Perfluorocarbon nanodroplets (NDs) have been widely investigated as both diagnostic and therapeutic agents. There remains, however, a challenge in generating NDs that do not vaporize spontaneously but can be activated at ultrasound pressures that do not produce unwanted bioeffects. In previous work, it has been shown that phospholipid-coated perfluorobutane (PFB) NDs can potentially overcome this challenge. The aim of this study was to investigate whether these NDs can promote drug delivery. Methods: A combination of high-speed optical imaging and passive cavitation detection was used to study the acoustic properties of the PFB-NDs in a tissue mimicking phantom. PFB-NDs were exposed to ultrasound at frequencies from 0.5 to 1.5 MHz and peak negative pressures from 0.5 to 3.5 MPa. In addition, the penetration depth of two model drugs (Nile Red and 200 nm diameter fluorescent polymer spheres) into the phantom was measured. Results: PFB NDs were found to be stable in aqueous suspension at both 4°C and 37°C; their size remaining unchanged at 215 ± 11 nm over 24 h. Penetration of both model drugs in the phantom was found to increase with increasing ultrasound peak negative pressure and decreasing frequency and was found to be positively correlated with the energy of acoustic emissions. Extravasation depths >1 mm were observed at 0.5 MHz with pressures <1 MPa. Conclusion: The results of the study thus suggest that PFB NDs can be used both as drug carriers and as nuclei for cavitation to enhance drug delivery without the need for high intensity ultrasound.